Prevalence and antimicrobial resistance of uropathogens in Karachi, Pakistan - Fatima, Ambreen; Iffat, Wajiha; Dawood, Kamran; Sarfaraz, Sabahat; Hussain, Zeb; Siddiqui, Hira Zafar; Gajdács, Márió (Acta Biologica Szegediensis, 2023)
Urinary tract infections (UTIs) are one of the major healthcare concerns causing an alarmingly high medical and financial burden in both developing and developed countries. There is a significant rise in multidrug-resistant (MDR) uropathogens, both in hospitalized and community settings, which threatens safe and effective therapy of these infections. The increased rates of resistance in UTIs requires the continuous surveillance of uropathogens in the specific area to inform safe and effective therapy. The present, retrospective, cross-sectional, descriptive study was carried out using samples collected between 01/06/2019 and 31/05/2020 in Karachi, Pakistan, during which, n = 1500 urine samples were collected. The samples were processed on Cystine Lactose Electrolyte Deficient (CLED) agar, identification was carried out by using standard biochemical tests and API 20E/20NE strips. Antimicrobial susceptibility testing was performed using standard disk diffusion test protocol, as per Clinical and Laboratory Standards Institute (CLSI) guidelines. Overall, n = 1189 urine samples (79.27%) showed significant bacterial growth. The median age of affected patients was 56 years (range: 1-100) with n = 811 females (68.21%), with patients between 61-80 years (n = 384; 32.29%) as the most numerous age group. Regarding uropathogen distribution, the overwhelming majority were Gram-negative bacteria (n = 986; 82.93%), the most common causative agent being Escherichia coli (n = 648; 54.49%), followed by Klebsiella spp. (n = 206; 17.33%) and Enterococcus spp. (n = 118; 9.92%). Resistance rates were highest for the tested fluoroquinolones (>70% for most species), trimethoprim-sulfamethoxazole, broad-spectrum penicillins, and cephalosporins, while fosfomycin, carbapenems and colistin largely retained their efficacy. The mitigation of UTIs and the emergence of resistance may be impeded by taking appropriate measures for the better management of patients; these interventions include improvements in the treatment recommendations, provision of health education, and continuous antimicrobial surveillance.